Remaining Service Life Struktur Conveyor C pada Tambang Batubara PT XYZ di Kabupaten Banjar, Provinsi Kalimantan Selatan - Elviya Yeni; Elfida Moralista; Yuliadi (UNISBA Press, 2022)
Abstract. Conveyor is one of the tools of transportation used in the mining industry, both for mining activities and for processing minerals. Conveyor structure made of carbon steel material that is prone to corrosion as a result of the influence of the environment, so it can be damaged and reduce the Remaining Service Life of the conveyor structure. This research was conducted to determine the type of corrosion, corrosion control methods, Corrosion Rate, and Remaining Service Life of the conveyor structure. In this study, the method of measuring the thickness reduction of the conveyor structure. The actual thickness measurement is carried out on a conveyor structure 90 meter long test points using a Smart Sensor Ultrasonic Thickness Gauge TT 130. The average rainfall is 206.94 mm/year, the relative humidity 82.17%, and the average temperature is 25.92ºC. The type of corrosion that occurs in the conveyor structure is uniform corrosion. The corrosion control method used is a three layers system coating method, namely the primary coating using Seaguard 5000, the intermediate coating using Sherglass FF, and the top coating using Aliphatic Acrylic Modified Polyurethane. Corrosion Rate ranges from 0.1586 to 0.3043 mm/year which is included in the good category according to the table of relative corrosion resistance of steel. The design life of the conveyor structure is 15 years and the service life is 7 years, while the Remaining Service Life from the calculation results ranges from 6.89 to 11.90 years, thus 7 of 25 or 28% of the test point is predictet won’t be able to reach its design life. Abstrak. Conveyor ialah salah satu alat angkut yang digunakan dalam industri pertambangan, baik untuk keperluan aktivitas penambangan maupun pada aktivitas pengolahan bahan galian. Struktur conveyor yang terbuat dari material baja karbon yang rawan mengalami korosi sebagai akibat pengaruh dari lingkungannya, sehingga dapat mengalami kerusakan dan mengurangi Remaining Service Life struktur conveyor tersebut. Penelitian ini dilakukan untuk mengetahui jenis korosi, metode pengendalian korosi, Corrosion Rate, dan Remaining Service Life struktur conveyor. Pada penelitian ini menggunakan metodologi pengukuran pengurangan ketebalan struktur conveyor. Pengukuran tebal aktual dilakukan pada struktur conveyor sepanjang 90 meter yang terdiri atas 25 test point menggunakan alat Smart Sensor Ultrasonic Thickness Gauge TT 130. Kondisi lingkungan pada daerah penelitian pada tahun 2015 – 2019 mempunyai curah hujan rata-rata 206,94 mm/tahun, kelembapan relatif rata-rata 82,17%, dan temperatur rata-rata 25,92ºC. Jenis korosi yang terjadi pada struktur conveyor adalah korosi merata. Metode pengendalian korosi yang digunakan adalah metode coating sistem three layers yaitu primer coating menggunakan Seaguard 5000, intermediate coating menggunakan Sherglass FF, dan top coating menggunakan Aliphatic Acrylic Modified Polyurethane. Corrosion Rate berkisar 0,1586 – 0,3043 mm/tahun yang termasuk pada kategori good berdasarkan tabel ketahanan korosi relatif baja. Umur desain struktur conveyor tersebut 15 tahun dan umur pakai 7 tahun, sedangkan Remaining Service Life dari hasil perhitungan berkisar 6,89 – 11,90 tahun, dengan demikian sebanyak 7 dari 25 test point atau 28% test point diprediksi tidak dapat mencapai umur desainnya.